2001
DOI: 10.1097/00000374-200107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Adaptive Functioning of Children Prenatally Exposed to Alcohol to a Nonexposed Clinical Sample

Abstract: Young children who were exposed to alcohol prenatally show deficits in all domains of adaptive functioning. Although these deficits do not seem to differ from those exhibited by young children with psychiatric problems but no prenatal exposure, deficits in socialization behavior of prenatally exposed children may become more significant with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 18 publications
10
89
2
Order By: Relevance
“…Individuals with FASDs show deficits across multiple domains of adaptive functioning, including communication, socialization, and personal and community skills even when controlling for differences in intellectual functioning [Whaley et al, 2001;Jirikowic et al, 2008]. Parents of children with FASDs have observed their struggles to master tasks such as getting dressed, telling time, or counting change.…”
Section: Adaptive Skills Trainingmentioning
confidence: 99%
“…Individuals with FASDs show deficits across multiple domains of adaptive functioning, including communication, socialization, and personal and community skills even when controlling for differences in intellectual functioning [Whaley et al, 2001;Jirikowic et al, 2008]. Parents of children with FASDs have observed their struggles to master tasks such as getting dressed, telling time, or counting change.…”
Section: Adaptive Skills Trainingmentioning
confidence: 99%
“…Streissguth et al (37) identified adaptive behaviours as one of the most striking deficits in children with FASD. In another study on adaptive functioning, Whaley et al (38) found that socialization decreased with age (relative to the norm) among children two to 10 years of age with PAE. This study was not longitudinal and, thus, causal interpretations could not be made; however, it may be that some adaptive deficits in FASD become more pronounced with age.…”
Section: Outcomes Of Children With Fasdmentioning
confidence: 95%
“…They often display deficits in social skills (Carpenter, 2010;Kodituwakku, 2007;Rasmussen, Becker, McLennan, Urichuk, & Andrew, 2010;Whaley, O'Connor, & Gunderson, 2001) and are at risk for a variety of social-emotional challenges Drotar, Aylward, & Beebe, 2012;Greenbaum et al, 2009). These challenges are exhibited as both internalizing and externalizing behaviors (Graham et al, 2012;Greenbaum et al, 2009;Sood et al, 2001) and are observed by both parents and professionals across environments .…”
Section: Social Emotional Developmentmentioning
confidence: 99%